PENGARUH KESADARAN WAJIB PAJAK, PELAYANAN FISKUS, MOTIVASI, PENGETAHUAN WAJIB PAJAK, SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN KEGIATAN USAHA DAN PEKERJAAN BEBAS (Studi Di Wilayah KPP Pratama Semarang Candisari) (Students' Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the influence of taxpayer awareness, service tax authorities, motivas, knowledge of taxpayers and tax Sansi to compliance individual taxpayers who do business activity and work freely. The population in this study is mandatory individual conducting business and independent activities reported in the notification letter SPT Tax Office Pratma Candisari Semarang. Source of data in this study using primary data source of a questionnaire distributed to 80 respondents. The samples in this study is done by using convenience sampling technique based incidentally anyone who met with researchers, if respondent that incidentally found suitable as a source of data. Based on the results of tests performed can be seen that the awareness of taxpayers and tax penalties and significant positive effect on tax compliance private persons conducting business and work freely. As for the service tax authorities, motivation and knowledge taxpayers a significant negative effect on tax compliance private person who did business activity and work freely.Keywords: Awareness of The Taxpayer, The Service Tax Authorities, Motivation, Knowledge of The Taxpayer, The Tax Penalties and Compliance Individual Taxpayer